Crisis intervention handbook : assessment, treatment, and research - Roberts, Albert R. (Oxford University Press, 2005)
"This fully revised and expanded edition of the Crisis Intervention Handbook: Assessment, Treatment, and Research sets the standard of care for effective treatment of persons in acute crises or trauma." "This classic volume includes developments in crisis intervention practices and services, a field that was permanently altered on September 11, 2001. With 15 new chapters and a new section on disaster mental health and frontline crisis intervention strategies, this book gives professionals access to specific guidelines, practice techniques, protective factors, 60 case study applications, and evidence-based crisis intervention strategies that maximize opportunities for rapid assessment and crisis resolution. This highly practical, timely, and reader-friendly handbook addresses the full range of acute crisis episodes, including adolescent suicide, school violence, adult substance abuse, battering, sexually transmitted diseases, bioterrorism, and terrorist bombings."--Jacket